Input Traceability and Performance of Horticultural Firms in Kenya - Kingoto, Boniface Muli; Shale, Noor Ishmael; Wachiuri, Elizabeth (International Journal of Supply Chain Management, 2025)
Purpose: This study therefore sought to examine the effect of input traceability on performance of Horticultural Firms in Kenya. Methodology: This study adopted a cross-sectional survey research design. The unit of analysis for this study was 658 registered Horticultural firms in Kenya. The heads of procurement, quality assurance, production, information and communication technology as well as marketing departments in horticultural firms in Kenya formed the unit of observation. The target population was 3,290 heads procurement, quality assurance, production, information and communication technology as well as marketing departments from 658 registered Horticultural firms in Kenya. The sample size was determined using Slovin's Formula and stratified random sampling in the selection of 355 respondents from the target population. The study used both primary as well as secondary data. Secondary data was collection from the annual reports of different horticultural firms in Kenya. Primary data was obtained using semi-structured questionnaires. A pilot test was conducted to assess the validity and reliability of the research instrument. The semi-structured questionnaires generated qualitative and quantitative data. Thematic analysis was used to analyze qualitative data and the results will be presented in a prose form. Descriptive as well as inferential statistics were used in analysing quantitative data with the help of SPSS version 28.0 statistical software. Descriptive statistics comprised of frequency distribution, percentages, standard deviation and mean. Inferential statistics included correlation analysis and linear regression analysis. Findings: The study found that input traceability positively and significantly affects the performance of horticultural firms in Kenya. Unique Contribution to Theory, Practice and Policy: Horticultural firms should ensure that comprehensive tracking of the source of all inputs used guarantees quality and safety, which are important for consumer trust. In addition, regular audits of suppliers should be implemented to confirm adherence to ethical and sustainable practices.